A Cell Cycle-Related 13-mRNA Signature to Predict Prognosis in Hepatocellular Carcinoma - Zhou, Yang; Lei, Dengliang; Hu, Gangli; Luo, Fang (Frontiers in Oncology, 2022)
We aimed to propose a cell cycle-based multi-mRNA signature (CCS) for prognosis prediction and uncover new tumor-driver genes for Hepatocellular Carcinoma (HCC). Cell cycle-related gene sets and HCC samples with mRNA-Seq data were retrieved from public sources. The genes differentially expressed in HCCs relative to normal peritumoral tissues were extracted through statistical analysis. The CCS was constructed by Cox regression analyses. Predictive capacity and clinical practicality of the signature were evaluated and validated. The expression of the function-unknown genes in the CCS was determined by RT-qPCR. Candidate gene TICRR was selected for subsequent validation through functional experiments. A cell cycle-related 13-mRNA signature was generated from the exploratory cohort (TCGA, n=371). HCC cases were classified as high- vs. low-risk groups per OS (HR = 2.699). Significantly, the CCS exhibited great predictive value for prognosis in three independent cohorts, particularly in GSE76427 cohort (AUC=0.835/0.822/0.808/0.821/0.826 at 1/2/3/4/5 years). The nomogram constructed by integrating clinicopathological features with the CCS indicated high accuracy and practicability. Significant enrichment of tumorigenesis-associated pathways was observed in the high-risk patients by GSEA. RT-qPCR revealed that TICRR was overexpressed in HCC samples. Increased TICRR expression implied poor prognosis in HCC patients. Furthermore, depletion of TICRR in HCC cells decreased cell proliferation and the G1/S transition. In conclusion, the established 13-CCS had efficacy in prognostic prediction of HCC patients. Additionally, TICRR was demonstrated as a tumor-driver gene for this deadly disease.